Espaço e criminalidade em favelas de Belo Horizonte: um estudo sob a ótica da segregação e do controle socioespaciais - Vera Cristina de Sousa Lima (2010)
This dissertation aims at discussing and investigating the relations between crime and socio-spatial configuration of the slums of Belo Horizonte, considering the internal conditions of the settlements and their participation in the urban environment. Normally segregated in relation to its surroundings, they can be considered rich when it comes to the appropriation of spaces and internal social relations. The slums have asocio-spatial configuration which seems to work ambiguously in relation to different types of crimes. The area of the slums, with their diverse forms of appropriation, either by movement or by occupation, promotes natural surveillance exercised by its own residents, but is quite unfavorable to the presence of strangers, as it is unfamiliar anddifficult to understand. If on one hand it seems to inhibit certain types of crimes such as thefts and burglaries, on the other it seems to encourage the emergence of territoriality and the reversal of attributes conducive to social control in favor of criminal groups, such as those related to the drug traffic.